ISOLATION OF SECONDARY METABOLITE COMPOUNDS AND ANTIBACTERIAL ACTIVITIES TESTS FROM HEXANE EXTRACT OF STEM BARK MELOCHIA UMBELLATA (HOUTT) STAPF VAR. DEGRABRATA K - Usman, Usman; M, Muh Amir; Soekamto, Nunuk Hariani; Ahmad, Ahyar; Maulidiyah, Maulidiyah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This research aims to determine the content of secondary metabolite compounds and antibacterial activity of stem bark extract Melochia umbellata (Houtt) Stapf var. degrabrata. Methods: M. umbellata stem bark was extracted by maceration using methanol solvent. Separation and purification were done by partitioning, fractionation with chromatography, and recrystallization. Antibacterial activity test of hexane extract and third isolate from the bark of M. umbellata was done by agar diffusion method against bacterium Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Results: Phytochemical test showed that the hexane extracts of bark M. umbellata containing alkaloids and triterpenoids. Isolate D is a triterpenoid group compound, while FKa and FKb are steroid group compound. The hexane extract had the highest antibacterial activity against B. subtilis bacteria with inhibitory zone diameter 12.0 mm. Isolate D has a weak inhibitory effect on all test bacteria. The highest diameters inhibition zone of isolated FKa compound against B. subtilis and S. aureus bacteria was 18.0 mm and 13.0 mm, respectively, whereas, the highest diameter inhibition of zone FKb compound against B. subtilis bacteria with inhibitory zone was 12.0 mm. Conclusion: The FKa compound from the bark of M. umbellata has the potential to be antibacterial because the compound is able to inhibit bacterial growth with Ëƒ14 mm obstacle zone, especially against B. subtilis bacteria.